Draft Five Year Plan 1978-83 Government of Sikkim - Planning Commission (Planning Commission, 1978)
The process of alarmed economic development in Sikkim was- initiated as early as 1954 when a Seven Year Plan from 1954 to 1961 was formulated with the help of a technical team of the Planning Commission. This was followed up by three - Five Year Plans namely the Plans for 1961 to 1966, from 1966 to 1971 and from 1971 to 1976. Sikkim became a part of the Indian Union in May, 1975 when the fourth plan was drawing to a close.
Government of Sikkim, Planning and Development Department